2003
DOI: 10.1645/0022-3395(2003)089[0464:usotls]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of the Late Stages of Loma Salmonae Development in the Gills of Experimentally Infected Rainbow Trout

Abstract: The main objective of this investigation was to examine the ultrastructural features of gills from rainbow trout experimentally infected with Loma salmonae to determine the morphological events that occur during the late stages of development of this parasite. Peripheral distribution of the mature parasites inside round xenomas was observed at weeks 5 and 6 postexposure (PE), but eventually the parasite occupied the entire xenoma. Degenerative changes were observed only in immature parasites at week 7 PE, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The journey of the already dividing merozoites of L. salmonae ends (perhaps attracted by high O 2 levels) in the gill vascular spaces between the pillar cells (Rodríguez-Tovar et al 2003b). Then, either the pillar cell phagocytizes the parasite from the leucocyte and converts into a xenoma, or the extensions of the pillar cells retract to make space for the leucocyte, which turns into a xenoma itself.…”
Section: Route Of Fish Microsporidia From the Portal Of Entry To The mentioning
confidence: 99%
See 2 more Smart Citations
“…The journey of the already dividing merozoites of L. salmonae ends (perhaps attracted by high O 2 levels) in the gill vascular spaces between the pillar cells (Rodríguez-Tovar et al 2003b). Then, either the pillar cell phagocytizes the parasite from the leucocyte and converts into a xenoma, or the extensions of the pillar cells retract to make space for the leucocyte, which turns into a xenoma itself.…”
Section: Route Of Fish Microsporidia From the Portal Of Entry To The mentioning
confidence: 99%
“…Other leucocytes stay confined between the endothelium and basement membrane after having exited from the blood vessel. How much of tissue specificity and parasite tropism is involved in the case of L. salmonae and especially in other xenoma-forming microsporidia has still to be investigated (Rodríguez-Tovar 2003b).…”
Section: Route Of Fish Microsporidia From the Portal Of Entry To The mentioning
confidence: 99%
See 1 more Smart Citation
“…They did not find secondary xenomas developing near intact xenomas. Rodríguez-Tovar et al (2003) observed polar tubes extruded from spores of L. salmonae in rounded xenomas invaded by phagocytes. They proposed that this might be a mechanism for autoinfection, if nearby leucocytes could sustain infections if inoculated with sporoplasms via polar tubes.…”
Section: Figs 4-7 Microgemma Vivaresi In Taurulus Bubalismentioning
confidence: 85%
“…(Rodríguez-Tovar et al 2002). In the later study (Rodríguez-Tovar et al 2003) three types of xenoma were identified: rounded xenomas derived from pillar cells, flattened xenomas lying under the arterial endothelium, and irregular xenomas in connective tissue of the gill filament. Host reaction against the rounded xenomas was first observed at six weeks p.i.…”
Section: Figs 4-7 Microgemma Vivaresi In Taurulus Bubalismentioning
confidence: 96%